Editorial - Oniwide, Oyetola Olaoluwa (NIU Journal of Humanities, 2017)
This issue of KIU Journal of Humanities touches on development administration, educational administration, judicial administration entrepreneurship studies, human rights and gender studies, peace and conflict studies, extra-curricular activities as well as teaching and learning skills.  The first part of the Journal addresses issues in Development Administration such as Infrastructural Development, Fund Management, Taxation and Foreign Investments’ Framework. It is argued in one of the papers that social infrastructure development is capable of sustaining both social and economic growth and improved quality and living conditions of the society.  Social infrastructures remain the core element of social welfare.  Thus efforts to  raise social or public  welfare  must   necessarily  go  beyond the  traditional and limited approved of raising per capita income through agricultural development projects to the provision of  social basic needs  in term of  health and medical  facilities, potable water  and education . Governments are therefore advised to create a secure and enabling environment, free from corruption and undue interference, for the social infrastructures to thrive and contribute positively towards improving the welfare of the citizens. In part two, the importance of school development planning and job ethics in the educational sector are emphasized. It is suggested that workshops and seminars should be re-introduced to the teachers on the areas of teachers’ specializations and pedagogy in order to improve on the current effectiveness of the teachers. This would go a long way for the teachers to be more effective. It is also recommended that public and private universities should design and circulate code of conduct as well work ethics policy to cover senior and junior staff so as to enhance productivity among their staff. It has been observed that the administration of justice, in all countries and at all times is a subject broad and difficult, both in its operation and its influence. It is perhaps more indicative, a truer test, of the real temper and spirit, both of the government and the people of the state or country, than any other thing. This is why the papers in part three of this edition examine the role of the judiciary as the guardian or protector and the fundamental human rights of the citizens. It must also be mentioned that in the search for an economic development agenda/program that empowers people, entrepreneurial education is very important in order to achieve a sustainable development. Against this backdrop, the papers in part four amplify that central tenet. Theoretical, methodological and practical implications are discussed in the papers. In particular, the results recommended that entrepreneurship skills acquired through the mandatory entrepreneurship education programme for undergraduate students of tertiary institutions in Nigeria are an important consideration in helping self-employed graduates to enhance their career performance. In the Section on Peace and Conflict Studies, it is recommended that true federalism and genuine war against poverty and unemployment as well as massive infrastructural development as components of war for peace. In addition, government should embark on early monitoring of conflicts, probe the remote causes and be fair and just in transforming conflicts. This is drawn from the conclusion that the war for peace is insurmountable given that the right institutional and attitudinal framework is judiciously put in place and executed. It has been discovered that extra-curricular activities have the efficacy of creating positive social behavior, and given the finding that the pupils who highly participated in extra-curricular activities highly felt the confidence to perform well academically, and those who participated less in extra-curricular activities felt that they would not perform well academically, there is need for the two groups of pupils, the higher and lower participants in extra-curricular activities both to develop a feeling and confidence that they can perform very well academically, and hence work hard to achieve it. This is the argument of one the papers in the sections that focus on extra-curricular and social psychology. A few papers in this issue highlight ideas on how students can acquire teaching and learning skills. Based on the their findings, the papers in this section recommend among others that teachers should teach using video based instruction so as to encourage individualized learning. Also, the construction of ‘Integrated Classrooms’ that can house almost all teaching activities under one big roof is recommended. On the whole, this edition of KIU Journal of Humanities features many thought provoking articles. Some of these articles are empirical in nature while others have theoretical base. Each of them focuses on one specific social and management problem or the other; trying to proffer solutions to them. Readers are therefore advised to make proper use of the ideas presented by the various authors. Professor Oyetola O. Oniwide College of Humanities and Social Sciences, Kampala International University, P.O. Box 20000, Kampala, Uganda. editor.humanities@kiu.ac.ug